(untitled) (Journal of EAHIL, 2024)
This article describes the development of a tool to automate the translation of bibliographic database search strategies from the Ovid platform to a range of other platforms. The development of this Bibliographic Syntax Converter (BSC) tool took place as a collaboration between an information specialist and a team of coders during a two-day Hackathon. This collaboration illustrates the potential benefits of this kind of cross-disciplinary working. A discussion of the difficulties inherent in automating the translation of literature search syntax is also provided, using specific examples to demonstrate these difficulties. The article concludes with a brief consideration of the limitations of the BSC tool, and plans for future development.